If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3 = 2x + -1(3x + 2) + 6 Reorder the terms: 3 + 2x = 2x + -1(3x + 2) + 6 Reorder the terms: 3 + 2x = 2x + -1(2 + 3x) + 6 3 + 2x = 2x + (2 * -1 + 3x * -1) + 6 3 + 2x = 2x + (-2 + -3x) + 6 Reorder the terms: 3 + 2x = -2 + 6 + 2x + -3x Combine like terms: -2 + 6 = 4 3 + 2x = 4 + 2x + -3x Combine like terms: 2x + -3x = -1x 3 + 2x = 4 + -1x Solving 3 + 2x = 4 + -1x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add 'x' to each side of the equation. 3 + 2x + x = 4 + -1x + x Combine like terms: 2x + x = 3x 3 + 3x = 4 + -1x + x Combine like terms: -1x + x = 0 3 + 3x = 4 + 0 3 + 3x = 4 Add '-3' to each side of the equation. 3 + -3 + 3x = 4 + -3 Combine like terms: 3 + -3 = 0 0 + 3x = 4 + -3 3x = 4 + -3 Combine like terms: 4 + -3 = 1 3x = 1 Divide each side by '3'. x = 0.3333333333 Simplifying x = 0.3333333333
| c-4=18 | | 8x+3=3*2x-1 | | (6-x^2)-(36+12x+x^2)= | | (14+a)+16= | | w+-19=79 | | 6(3x+5)=2(6x-21)+6x | | 3=-5n+2 | | x^2-13x+53=17 | | 5+4x=-11x | | 12x+2=2(6x-4)+32 | | 54=2x^2-3x | | (-7)+7=0 | | 36a^2-12a+1= | | 5(3-2x)=3-4x | | -7921+15(198x-178)=0 | | y=4(3)-9 | | 5(7+8r)-2r=-9-6r | | -40-8a=-4(5a+7) | | 8-9x-2=-52+5x-12 | | 8y-(2y-3)=4 | | 7[3-4*(x+1)]+6[(2x+7)-8]=17x-333 | | 7x-4=2x+6x | | 10=8m-3m | | 6xy+2x-3y-1=0 | | 4x+8x=92 | | -4x-14=-6 | | 2(7-5)=14x-10 | | 2x+3(8)=12 | | -7936(198x-178)=0 | | 2.25m+3=4.125 | | 8.4x=12-3 | | 32+8x=6(x+8) |